A methodology to forecast the main non-dimensional performance parameters of pumps-as-turbines (PaTs) operating at Best Efficiency Point (BEP). (November 2020) - Renzi, Massimiliano; Nigro, Alessandra; Rossi, Mosè
Abstract: This work presents a model based on analytical equations to identify the Best Efficiency Point (BEP) of Pumps-as-Turbines (PaTs). The equations are developed exploiting an experimental data-set of 59 PaTs, obtained in both pump and turbine modes, in form of non-dimensional parameters. Data analysis shows a linear correlation between specific speeds in pump and turbine modes, as well as between specific diameters in both operating modes. In addition, the prediction of the PaT efficiency in turbine mode, whose evaluation is often disregarded in literature works, is presented: a second order polynomial equation to forecast the mechanical efficiency of PaTs in turbine mode is developed using the values of specific speed and mechanical efficiency in pump mode as independent variables. Performance experimental data of four PaTs, which were not used in the development of the model, are employed to validate and assess the accuracy of the proposed analytical equations. The prediction capability of the model is also compared to other four models available in literature. Results demonstrate a good forecast capability and a general better agreement with experimental data. A further improvement of the model can be achieved by extending the experimental data-set with additional PaTs typologies. Highlights: A BEP prediction model based on PaTs performance data is presented. Experimental BEP values of 59 PaTs available in literature were used. A set of equations, based on non-dimensional parameters, were presented. Data of six centrifugal pumps were used to validate the model. Results show the prediction accuracy is comparable to other models in literature.